Sosialisasi Siaga Bencana Dalam Penanggulangan Kegawatdaruratan pada Ibu Hamil Beresiko di wilayah kerja Puskesmas Pasar Ikan Kota Bengkulu: Sosialisasi Siaga Bencana Dalam Penanggulangan Kegawatdaruratan pada Ibu Hamil Beresiko di wilayah kerja Puskesmas Pasar Ikan Kota Bengkulu - Yulita Elvira Silviani; Desi Fitriani; Dewi Aprilia Ningsih; Ruri Maiseptya Sari; Metha Fahriani (Yayasan Ahmad Mansyur Nasirah, 2022)
Geographically, Indonesia is an archipelagic country located on the Ring of Fire, which is the confluence of three large tectonic plates, namely Indo Australia, Eurasia, and the Pacific, so that if one movement occurs, it can cause disasters such as earthquakes and tsunamis. The purpose of this community service activity is to provide knowledge to people living in the working area of the Pasar Ikan Health Center Bengkulu city. The method used in this community service is through outreach and outreach activities so that people in the Pasar Ikan Health Center work area can carry out emergency management of high-risk pregnant women in disaster situations. In addition, this activity provides basic training on procedures for evacuating pregnant women during disaster situations. This outreach and outreach activity is an activity or effort carried out to convey health messages to the public, groups or individuals. Based on the results of the activity, it was found that the results of understanding about disaster preparedness in emergency management for pregnant women after being given education obtained respondents who already understood as many as 78% respondents, and who did not understand 23% respondent and they are very enthusiastic participating in the activity. This can be seen from the response of the community who want to try to practice emergency handling by simulating the evacuation of pregnant women and the community also plans to form a disaster preparedness group. It is hoped that the community will immediately form a disaster alert group in the pasar ikan health center area because Bengkulu Province is indeed a disaster-prone area.